Does Helicobacter pylori Eradication Reduce the Incidence of Metachronous Gastric Cancer After Curative Endoscopic Resection of Early Gastric Cancer: A Systematic Review and Meta-Analysis. Issue 3 (March 2020) - Zhao, Bochao; Zhang, Jiale; Mei, Di; Luo, Rui; Lu, Huiwen; Xu, Huimian; Huang, Baojun
Abstract : Background: Whether Helicobacter pylori eradication could reduce the risk of metachronous gastric cancer remain controversial. In the present study, we performed a systematic review and meta-analysis to evaluate the preventive effect of H. pylori eradication on the occurrence of metachronous gastric cancer after curative endoscopic resection of early gastric cancer. Methods: The related studies were identified by searching PubMed and Embase databases. According to the H. pylori infection status and subsequent treatment, all patients were classified into H. pylori negative group, H. pylori eradication group and noneradication group. The relevant data were extracted and pooled effect size was assessed using a fixed effect model or a random effect model. Results: A total of 11 retrospective cohort studies and 3 randomized controlled trials were included in this meta-analysis. The results based on the cohort studies indicated that the risk of metachronous gastric cancer was significantly lower in H. pylori eradication group than in noneradication group (hazard ratios: 0.65, 95% confidence interval: 0.50-0.86, P =0.002; I 2 =0%). The pooled result of 2 randomized controlled trials demonstrated that the patients receiving anti- H. pylori treatment had a lower risk of metachronous gastric cancer than those who did not receive H. pylori eradication treatment (hazard ratios: 0.43, 95% confidence interval: 0.26-0.70, P =0.001; I 2 =0%). In addition, the occurrence of metachronous gastric cancer in H. pylori eradication group was not significantly different from that in H. pylori negative group. Conclusions: Successful H. pylori eradication may be useful for the prevention of metachronous gastric cancer after curative endoscopic resection of early gastric cancer. Thus, anti- H. pylori treatment should be considered for those patients with H. pylori infection after curative endoscopic resection. Abstract : Supplemental Digital Content is available in the text.